FREQUENCY OF EASY AND DIFFICULT LAPAROSCOPIC CHOLECYSTECTOMY FOR CHOLELITHIASIS - SIRAJ, MI; KAZIM, E; HAIDER, S; MEMON, ZA; IBRAHIM, F; MUQEET, A; HYDER, A; RAJPUT, IA; KHAN, NA (Biological and Clinical Sciences Research Journal, 2024)
The prevalence of gallstone disease is influenced by factors such as age, gender, and marital status. Ultrasonography is important for screening. Laparoscopic cholecystectomy (LC) is the standard treatment for symptomatic cholelithiasis, but some cases may require conversion to open surgery (OC). Preoperative ultrasound assessments, particularly the common bile duct (CBD) diameter, may help predict the difficulty of LC and prepare for potential complications. Objective: The objectives of this study are to assess the frequency of easy and difficult laparoscopic cholecystectomy in patients with cholelithiasis and to compare the mean diameter of the common bile duct between cases of easy and difficult laparoscopic cholecystectomy. Methods: This sctional study was conducted from February 10, 2023, to August 10, 2023, and included 170 patients (ages 18-60 years) undergoing laparoscopic cholecystectomy for cholelithiasis. Both genders were included. Variables such as age, gender, diabetes, hypertension, and cholecystectomy status were recorded. The mean and standard deviation (SD) were calculated for age and CBD diameter. An independent t-test was used to compare CBD diameters between easy and difficult LC cases. Chi-square tests were applied to control for effect modifiers. Results: The mean age of the patients was 52.32 ± 4.89 years. Other patient characteristics included an average height of 162.90 ± 9.25 cm, weight of 75.95 ± 12.32 kg, and BMI of 27.47 ± 4.72. The common bile duct diameter was 4.55 ± 1.42 mm. Gender distribution showed 54.7% male and 45.3% female patients. Of the 170 patients, 84 (49.4%) were classified as easy LC cases, while 86 (50.6%) were classified as difficult. The mean CBD diameter was significantly different between the two groups, measuring 3.54 ± 1.03 mm in easy cases and 5.52 ± 1.02 mm in difficult cases (p = 0.001). Conclusion: This study highlights the importance of preoperative assessment of common bile duct diameter in predicting the difficulty of laparoscopic cholecystectomy. Patients with a larger CBD diameter are more likely to experience a difficult LC, emphasizing the need for personalized surgical planning. These findings underscore the value of preoperative ultrasonography in optimizing patient outcomes and reducing the risk of conversion to open surgery.